Plasma generation by dielectric resonator arrays. (12th May 2016) - Dennison, Stephen; Chapman, Adam; Luo, Wei; Lanagan, Michael; Hopwood, Jeffrey
Abstract: Arrays of dielectric resonators—illuminated by an antenna—are used to ignite and sustain multiple microwave plasmas in parallel. Calcium titanate cylindrical resonators were arranged in a linear array with separation distances between 0.5 and 5 mm. The operating frequency was near the HEM111 resonance of 1.1 GHz. Paschen curves of the breakdown field and voltage in argon atmosphere are consistent with parallel plate microwave breakdown except within discharge gaps of 1 mm or less. Sustaining of argon plasma between 0.5 Torr and 1 atm within the array is found to alter the electromagnetic scattering from the dielectric resonators, suggesting applications in plasma-reconfigurable metamaterials and photonic crystals.